Surgical Outcome after Posterior Fossa Decompression with and without Duraplasty in Adult Chiari Malformation Type-I - Tariq Awad (Egyptian Spine Association, 2016)
Background Data: Adult Chiari malformation is a heterogeneous group of conditions, with the underlying commonality of disruption of normal CSF flow through the foramen magnum. Some cases are congenital, but others are acquired. The optimal surgical treatment of adult Chiari malformation type-I is unclear. Purpose: To evaluate the operative and postoperative results of extradural and intradural approaches in the treatment of Chiari malformation type-I. Study Design: A descriptive retrospective clinical case study. Patients and Methods: Twenty patients underwent surgery for adult Chiari malformation type-I. They were divided into two groups; posterior fossa decompression group and posterior fossa decompression with duroplasty group. Each group included 10 patients. They were operated between 2008 and 2015. Participants were evaluated pre-operatively and post-operatively every three months. Operative time, hospital stay and complications were assessed. The clinical outcomes were compared between the two groups using The Chicago Chiari Outcome Scale. Results: No statistically significant differences were found between the decompression and duroplasty groups with regard to demographics, preoperative symptoms, radiographic characteristics, and clinical outcomes. However, the operative time, hospital stay and aseptic meningitis were higher in the duroplasty group.Conclusion: The clinical outcome of posterior fossa decompression is nearly identical to that of posterior fossa decompression with duroplasty in adult patients with Chiari type-I; however, the operative time, hospital stay and complication rate is higher in duroplasty group. (2016ESJ113)